Peran Ukhuwah Islamiyah sebagai mekanisme Koping terhadap Urban Loneliness Mahasiswa Perantauan di UIN Walisongo Semarang - Inayah Dhivaningtyas; Iffa Mustaqimah; Sri Isnani Setiyaningsih (Ahad: Multidisciplinary Journal of Islamic Studies, 2026)
The phenomenon of urban loneliness among migrant students has become a contemporary social challenge that threatens mental well-being and social cohesion on campus, particularly at UIN Walisongo Semarang. This study aims to analyze the role of Ukhuwah Islamiyah as a coping mechanism in overcoming this social alienation, as well as integrating religious values within the framework of Civic Education to strengthen national solidarity. This study uses a descriptive qualitative approach with a case study method through observation and in-depth interviews with migrant students at UIN Walisongo, supported by a review of academic literature for the 2020–2025 period. The analysis results indicate that urban loneliness is triggered by migration factors, urban individualism, and impersonal digital communication patterns. The research findings confirm that Ukhuwah Islamiyah functions significantly as a coping mechanism through strengthening hablum minannas and activating mosque-based communities that facilitate meaningful social interactions. From a PPKN perspective, this practice of solidarity reflects the practice of the Third Principle of Pancasila, namely "Indonesian Unity," which acts as a glue for national integration amidst the diversity of students' regional backgrounds. This research provides theoretical and practical contributions to the development of inclusive and solution-oriented civic character (civic virtue) in facing the challenges of modern urban life.